The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.3402/tellusa.v39i3.11757
|View full text |Cite
|
Sign up to set email alerts
|

The large-scale circulation in the Skagerrak; interpretation of some observations

Abstract: Instantaneous velocity observations with high-space resolution at two sections in the Skagerrak has been repeated during the years 1975 to 1977. The velocity observations are presented together with hydrographic data. The mean currents show a cyclonic circulation. Apart from a narrow baroclinic coastal current, the mean velocities generally increase towards the bottom. The mean velocities at the bottom are highest close to and below the sill depth. In the upper layers, the direction of the circulation occasion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 2 publications
6
56
0
Order By: Relevance
“…< 100 m. Eisma & Kalf (1987) found that suspended matter concentrations in the bottom water are similar to those in the surface and that velocity of the currents going into Skagerrak can be up to 15 cm S-' down to 100 m water depth (Rodhe 1987). It can be noted that an unbalance between carbon input and respiration has also been found by others, e.g.…”
Section: Sedimentation and Respirationmentioning
confidence: 67%
“…< 100 m. Eisma & Kalf (1987) found that suspended matter concentrations in the bottom water are similar to those in the surface and that velocity of the currents going into Skagerrak can be up to 15 cm S-' down to 100 m water depth (Rodhe 1987). It can be noted that an unbalance between carbon input and respiration has also been found by others, e.g.…”
Section: Sedimentation and Respirationmentioning
confidence: 67%
“…Two major current systems affect the coastal area; the Baltic Current runs north, parallel to the coast, bringing low salinity surface water, whereas more saline water from the North Sea and Atlantic Ocean flows through the Skagerrak towards the Swedish coast in the Jutland Current. Hence, the coastal water is stratified in terms of salinity, and a pronounced halocline is present (Rodhe 1987, Lindahl 1995. The coastline has a variety of fjord systems.…”
Section: Methodsmentioning
confidence: 99%
“…Two major current systems affect the Skagerrak coastal area: the low saline surface Baltic current running north parallel to the coast, and the central Skagerrak water circulation pattern resulting in an inflow of more saline North Atlantic water. Hence, the coastal water is stratified in terms of salinity and a pronounced halocline is present (Rodhe 1987, Lindahl 1995. Within Nycklebyviken is a blue mussel farm of approximately 4500 m 2 (Fig.…”
Section: Methodsmentioning
confidence: 99%